Rotating Rayleigh-Taylor instability - Scase, Matthew M.; Baldwin, Kyle A.; Hill, Richard J.A. (American Physical Society, 2017)
The effect of rotation upon the classical Rayleigh-Taylor instability is considered. We consider a two-layer system with an axis of rotation that is perpendicular to the interface between the layers. In general we find that a wave mode’s growth rate may be reduced by rotation. We further show that in some cases, unstable axisymmetric wave modes may be stabilized by rotating the system above a critical rotation rate associated with the mode’s wavelength, the Atwood number and the flow’s aspect ratio.